The modern features of clinical picture, diagnostics and therapy of patients with eczema - L. A. Yusupovа; E. I. Yunusovа; Z. Sh. Garaeva; G. I. Mavlyutova; E. V. Bildyuk; A. N. Shakirova (Лечащий Врач, 2021)
The article presents data on eczema — a recurrent inflammatory dermatosis with polymorphism of rashes formed under the influence of exogenous or endogenous risk factors. Etiological and pathogenic mechanisms leading to the development of eczema are given, the clinical picture of different forms of the disease is described in detail. The article reveals the information about the methods of diagnostics and therapy for these patients.